Nonfunctionalized Cation of an Ionic Liquid as a Ligand in the Synthesis of a New Coordination Compound and Assessment of Its Biological Activity - Getinet Tamiru Tigineh; Atakilt Abebe (Bioinorganic Chemistry and Applications)
Literature evidences reveal the affinity of ionic liquids for biomembranes that they are readily absorbed into the cell, resulting in a variety of biological effects, including broad antibacterial potential and anticancer activity. Recent research directions considered the ions of this class of compounds as a new choice of ligands in the synthesis of transition metal complexes for various applications. Based on this, the present work reports the synthesis, structural characterization, and in vitro antibacterial activities of a tetrahedral hexacationic Co(II) complex formed by coordinating with the cation of an ionic liquid, N-butyl-4,4-bipyridinium bis(trifluoromethylsulfonyl)amide ([C4Bip][Tf2N]). It has been demonstrated by the isolation and characterization of tetrakis-(N-butyl-4,4′-bipyridinium)cobalt(II)dichloride-tetrakis-(bis(trifluoromethylsulfonyl)amide, ([(C4Bip)4Co]Cl2(Tf2N)4). The ligand and complex are characterized spectroscopically (1H, 13C, and 19F NMR, ESI MS, ICP OES), and by CHNS elemental analysis, halide estimation, and conductivity studies. The antibacterial activities of the compounds against two bacteria, Klebsiella pneumoniae (K. pneumoniae) and Staphylococcus aureus (S. aureus), are screened using the agar well-diffusion method and were compared with a reference (gentamicin). The metal complex demonstrated better inhibition than the ionic liquid and the reference.